A COMPARATIVE EVALUATION OF LOCAL ANESTHETIC EFFECT BETWEEN LIGNOCAINE AND LIGNOCAINE ADMINISTERED WITH EPINEPHRINE IN HEALTHY CHILDREN - Zhou, Yan; Qiu, Jing (Acta biochimica Polonica, 2019)
Lignocaine, first amino amide–type local anesthetic when combines or co-administered with Epinephrine, an sympathomimetic amine, allows larger doses for numbing, to decrease bleeding, and to make the numbing effect last longer. The present study focuses on measures to prove this activity in patients with abdominal surgery. Liposomal formulations of Lignocaine and Lignocaine plus epinephrine were prepared by thin film evaporation method. The formulation was injected successfully as liposomal infusion. Thus prepared liposomes were found to be fit for drug delivery when evaluated as per physicochemical parameter. The smooth, even surfaced liposomes with PDI of 0.298 (p<0.05) were found to be efficient in delivering drug when tested In-vitro (Lignocaine as single drug 93.78% and from combined dosage 96.29% Lignocaine with 94.62 % of release of Epinephrine). The randomized, controlled trial conducted on population of children undergone abdominal surgery and grouped into three depending upon the type of formulation they received. Three groups of subjects were made, first receiving Lignocaine liposomal infusion only; second with Lignocaine plus Epinephrine liposomal infusion; third group kept control which received saline solution only. The serum Cortisol concentration was found to be least in Group II in compare to Group I. Similarly end point measurements like cool sensation, warm sensation, hot pain, sensory blockade test showed the superiority of combination of Lignocaine with Epinephrine in lowering pain threshold. The result obtained from above study proved that Epinephrine markedly enhances the Local anesthetic activity of Lignocaine. KEYWORDS: Child Anesthesia, Epinephrine, Lignocaine, Liposomal Infusion, Local anesthetic.